New data on the morphology of Ascarophis parupenei (Nematoda: Cystidicolidae), an intestinal parasite of the marine fish Parupeneus indicus in the Indian Ocean, revealed by SEM - Moravec, František (Systematic parasitology, 2024)
Scanning electron microscopy studies of three paratype specimens (two males and one female) of Ascarophis parupenei Moravec, Orecchia & Paggi, 1988, an intestinal parasite of the marine fish Parupeneus indicus (Shaw) in the Indian Ocean, made it possible to redescribe in detail the cephalic structures of this nematode as well as the morphology of the male caudal end. The presence of non-bilobed sublabia, phasmids in both males and females, bifurcated deirids, well-developed precloacal cuticular ridges (area rugosa) and a ventral median caudal protuberance in the male are reported in this species for the first time. The general morphology and measurements of A. parupenei somewhat resemble those of Rasheedia novaecaledoniensis Moravec & Justine, 2018 described from the same host species (P. indicus) from off New Caledonia, but both species clearly differ from each other by the shape and structure of pseudolabia and the anterior portion of the digestive tract, belonging thus to different nematode families (Cystidicolidae and Physalopteridae, respectively).
Keywords: Animals; mužské pohlaví; Microscopy, Electron, Scanning; Spiruroidea; ženské pohlaví; druhová specificita; Perciformes; zvířata; Species Specificity; Fishes; ryby; Female; Indický oceán; Male; Indian Ocean; mikroskopie elektronová rastrovací